A model for reticular dysgenesis shows impaired sensory organ development and hair cell regeneration linked to cellular stress - Alberto Rissone; Erin Jimenez; Kevin Bishop; Blake Carrington; Claire Slevin; Stephen M. Wincovitch; Raman Sood; Fabio Candotti; Shawn M. Burgess (The Company of Biologists, 2019)
Mutations in the gene AK2 are responsible for reticular dysgenesis (RD), a rare and severe form of primary immunodeficiency in children. RD patients have a severely shortened life expectancy and without treatment die, generally from sepsis soon after birth. The only available therapeutic option for RD is hematopoietic stem cell transplantation (HSCT). To gain insight into the pathophysiology of RD, we previously created zebrafish models for Ak2 deficiencies. One of the clinical features of RD is hearing loss, but its pathophysiology and causes have not been determined. In adult mammals, sensory hair cells of the inner ear do not regenerate; however, their regeneration has been observed in several non-mammalian vertebrates, including zebrafish. Therefore, we used our RD zebrafish models to determine whether Ak2 deficiency affects sensory organ development and/or hair cell regeneration. Our studies indicated that Ak2 is required for the correct development, survival and regeneration of sensory hair cells. Interestingly, Ak2 deficiency induces the expression of several oxidative stress markers and it triggers an increased level of cell death in the hair cells. Finally, we show that glutathione treatment can partially rescue hair cell development in the sensory organs in our RD models, pointing to the potential use of antioxidants as a therapeutic treatment supplementing HSCT to prevent or ameliorate sensorineural hearing deficits in RD patients.